STAKEHOLDER MAPPING DALAM PELAKSANAAN COMMUNITY TOURISM COLLABORATIVE GOVERNANCE (CTCG) DI DESA MARON WONOSOBO - Ika Nur Afni (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2021)
Maron Village, Garung District, Wonosobo Regency applies the concept of Community Tourism Collaborative Governance (CTCG) in the management of existing tourism. This concept to develop the potential and increase the socio-economy in Maron Village. However, in its implementation, not all stakeholders have the same role in tourism management in Maron Village. So this paper will describe how stakeholders mapping is in tourism management in Maron Village. As well as what things make the role of stakeholderss unequal in developing tourism in Maron Village, Garung District, Wonosobo Regency. The research is descriptive with a qualitative approach. The data obtained in this study are primary and secondary data obtained from in-depth interviews and Focus Group Discussions (FGD) with various stakeholderss involved in Community Tourism Collaborative Governance (CTCG). The results show that the things that divide roles uneven are (1) there is still a tug of war between stakeholderss, especially from the Tourism and Culture Office of Wonosobo Regency with several communities around Menjer Lake so that some communities do not participate in its management. (2) Ownership of several tourist attraction objects such as gethek and selfie spots still belongs to individuals. (3) The loss of public trust in the government so that the community prefers to support local community activities which are the initiators of tourism management in Maron Village.